Analisis Sistem Informasi dengan Menggunakan Variabel Model Penerimaan Teknologi dan Tingkat Kepercayaan - Suyanto, Suyanto; Wardani, Kiky Rizky (JURNAL ILMIAH MATRIK, 2015)
Website is one of the means to deliver sustainable information , it is used by the government to make the site as a tool for efficient and effective in conveying the information. However , the government website has not been optimized in use by the user, need to evaluate the level of acceptance of the site which can certainly increase the use of the website . This study uses the TAM variables perceived ease to use, perceptions of the benefits and common uses of the added variable of trust. This study researched by distributing questionnaires to people in Palembang, the results of the data processed with maximum likehood estimation techniques. The results of the hypothesiswill encourage the use of government websites. It can be concluded that when the perceived information useful and credible information (unconfirmed) will result in a persons desire to use an information system.